Comparison of Inheritance Law in Islamic Law and Civil Law - Anggi Wicaksono; Zainal Arifin Hosein (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This study aims to analyze the comparative law on inheritance in the Islamic legal system, civil law, and its impact on Indonesian implementations. The research method used is normative juridical with a statute approach and a conceptual approach, which focuses on analyzing applicable legal documents and norms. This study discusses the characteristics of each legal system, including differences in the distribution of inheritance, the obligations of heirs to the debts of the testator, and the inheritance mechanism regulated in the Civil Code (KUHPerdata) and Islamic inheritance law. Furthermore, this study explores the impact of implementing the two legal systems in Indonesia, considering the diversity of Indonesian society that influences the implementation of inheritance law. The results are expected to provide deeper insight into how the two legal systems interact and influence inheritance practices in Indonesia.